PRINCIPLES OF PSYCHOLOGICAL EXPERTISE OF EDUCATION - Yablonsky, Andriy; Yatsenko, Liana (Mountain School of Ukrainian Carpaty, 2021)
The article is devoted to substantiation of the principles of humanitarian and psychological expertise of education, for which the basic provisions of general psychology and other branches of psychological science are basic. The author refers to the coverage of theoretical aspects of scientific support of humanitarian and psychological expertise of education, which determine the basic principles of its implementation. The system of training of practical psychologists make effective enough to respond to the urgent needs of social practice in preparation for the practical psychologists activity, understand its contents, methods and forms of implementation. At the same time, the existing socio-cultural reality requires a rethinking of domestic and foreign experience, research strategies, models, theoretical and methodological, methodic’ practical training psychologists to conduct humanitarian and psychological examination. The article deals with the principles of humanitarian and psychological expertise of education, for which the base is the fundamental position of psychological science and practice. Presented by the principle of systematic study campaign, the implementation of which is aimed at analysis educative practice with the whole set of internal and external relations, in which it exists as an integrated system. Principle of tiered analysis allows us to consider some of the middle of the system and to determine their place and role in system. Principe of the determinism, which is a feature of the implementation of the psychological analysis of each obtained during the examination of the phenomenon, not only provides a statement of each obtained in the course of the examination of the phenomenon, but and analysis of the reasons for its existence. The principle of objectivity is purposed to insight into the phenomenon at the same time without making that is typical to the researcher – the inner participant of the conception knowledge process. The principle of interdisciplinary is based on the idea of the integrity of the nature of the educational sphere as the humanitarian system, which is based on the expert study also acquires the characteristics of interdisciplinary. The principle of practical orientation suggests the importance and the need to bridge the gap between theoretical knowledge in practice, taking place in the psychological and pedagogical sciences. The further research will be scheduled in the direction of the theoretical and methodological understanding of humanitarian and psychological expertise of education.